2021
DOI: 10.1063/5.0062135
|View full text |Cite
|
Sign up to set email alerts
|

Fermi level controlled point defect balance in ion irradiated indium oxide

Abstract: Fermi level controlled point defect balance is demonstrated in ion irradiated indium oxide (In 2 O 3 ). Specifically, our observations can be sub-divided into the formation of isolated Frenkel pairs and secondary defects, correlated with an increase and decrease in resistance, respectively. Importantly, by considering the net charge contribution from the most energetically stable Frenkel pair configurations, we explain the data trends for low doses and determine an upper limit for the Fermi level pinning. More… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…The fact that proton damage does not produce the hysteresis in I-V characteristics seen for gamma irradiation in these structures indicates that the reversible resistivity changes seen in other irradiated oxides is not occurring. For example, Borgersen et al [30,32] reported that irradiation of the related oxide, In 2 O 3 , with low doses of Si ions or and long UV exposures result in similar resistivity drops, interpreted as irradiation/illumination assisted desorption of oxygen containing species from the surface. This was consistent with the effect of post-irradiation exposure of the samples to an oxygen atmosphere partially restoring the resistivity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that proton damage does not produce the hysteresis in I-V characteristics seen for gamma irradiation in these structures indicates that the reversible resistivity changes seen in other irradiated oxides is not occurring. For example, Borgersen et al [30,32] reported that irradiation of the related oxide, In 2 O 3 , with low doses of Si ions or and long UV exposures result in similar resistivity drops, interpreted as irradiation/illumination assisted desorption of oxygen containing species from the surface. This was consistent with the effect of post-irradiation exposure of the samples to an oxygen atmosphere partially restoring the resistivity.…”
Section: Resultsmentioning
confidence: 99%
“…While the Ga 2 O 3 is known to be relatively resistant to total dose damage [27,28], large reversible changes in current-voltage characteristics of the heterojunctions have been observed after Co-60 gamma ray exposure which appears to be due to conductivity changes in the NiO [29]. Other low dose ion irradiated oxides have also shown enhanced conductivity which in some cases has been linked to irradiation/illumination assisted desorption of oxygen containing species from the oxide surface [30][31][32][33]. There have also been recent demonstrations of single event burnout (SEB) in Ga 2 O 3 rectifiers [34], while simulations show the SEB threshold voltage of conventional Ga 2 O 3 MOSFETs is lower than that of state-of-the-art AlGaN/GaN HEMTs [35,36].…”
Section: Introductionmentioning
confidence: 99%
“…However, a change over several orders of magnitude is much more likely to be expected for n than for μ. [ 19 ]…”
Section: Resultsmentioning
confidence: 99%
“…Studies have been performed showing that intentionally damaged In 2 O 3 films display similar electrical properties with increasing damage regardless of their initial state (undoped, donor‐doped, or acceptor‐doped). [ 19 ] This is justified by the fact that the Fermi level in these samples is eventually raised into the conduction band by introduced intrinsic defects and defect complexes. Especially in the case of compensation doped samples (with Mg, as in this work as well) this leads to a drastic increase of the charge carrier density and, thus, decrease of the resistivity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation